2022
DOI: 10.3389/fneur.2021.809438
|View full text |Cite
|
Sign up to set email alerts
|

Glymphatic Dysfunction in Patients With End-Stage Renal Disease

Abstract: BackgroundWe aimed to compare glymphatic dysfunction between patients with end-stage renal disease (ESRD) and healthy controls and analyze the correlation between the glymphatic function and clinical characteristics using the diffusion tensor image analysis along with the perivascular space (DTI-ALPS) index.MethodsWe prospectively enrolled neurologically asymptomatic 49 patients with ESRD undergoing dialysis and 38 healthy controls. Diffusion tensor image was conducted using the same 3T scanner, and the DTI-AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The findings of our study are consistent with the results of previous studies that confirmed glymphatic system dysfunction in patients with non-dialysis CKD 17 and ESKD patients on dialysis [ 16 ]. Previous studies also showed that patients with ESKD have a higher prevalence of cognitive impairment with worse results on neurocognitive tests compared to the general population [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of our study are consistent with the results of previous studies that confirmed glymphatic system dysfunction in patients with non-dialysis CKD 17 and ESKD patients on dialysis [ 16 ]. Previous studies also showed that patients with ESKD have a higher prevalence of cognitive impairment with worse results on neurocognitive tests compared to the general population [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Impairment of the glymphatic system has been implicated in the pathogenesis of cognitive impairment in various neurological disorders [ 6–8 ]. In our previous studies, patients with various stages of chronic kidney disease (CKD) showed - abnormalities in the glymphatic system [ 16 , 17 ]. However, it was unclear whether these abnormal findings of the glymphatic system could be improved through KRT, or not.…”
Section: Introductionmentioning
confidence: 99%
“…With evidence from bench to clinical, impairment of aquaporin function leads to kidney diseases [ 40 ]. Impaired glymphatic activity was observed in chronic kidney disease, from mild to advanced stages [ 41 , 42 ]. Besides, our results also support this renal-brain association in water metabolism that blood Cr and BUN correlated with the DTI-ALPS index.…”
Section: Discussionmentioning
confidence: 99%
“…The averaged diffusivities were obtained in each ROI, excluding the maximum and minimum values, from among the various voxels for each fiber on the same x, y, and z axes (projection, association, and subcortical fibers). The DTI-ALPS index was derived using the formula below ( 6 , 15 , 17 ):…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it can be expected that dysfunction of glymphatic system may be present in patients with CKD. The DTI-ALPS index has previously been utilized to indicate glymphatic system dysfunction in ESRD patients, and the method's feasibility for assessing glymphatic system function in ESRD patients was verified ( 15 ). However, no research has been done on the function of the glymphatic system in patients with early CKD.…”
Section: Introductionmentioning
confidence: 99%